2023
DOI: 10.7554/elife.81549
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a transparent killifish line through multiplex CRISPR/Cas9mediated gene inactivation

Abstract: Body pigmentation is a limitation for in vivo imaging and thus for the performance of longitudinal studies in biomedicine. A possibility to circumvent this obstacle is the employment of pigmentation mutants, which are used in fish species like zebrafish and medaka. To address the basis of aging, the short-lived African killifish Nothobranchius furzeri has recently been established as a model organism. Despite its short lifespan, N. furzeri shows typical signs of mammalian aging including telomere shortening, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…More recently, longer CRISPR/Cas9-mediated knock-in insertions (~1 kb) were achieved in killifish (in F0 individuals) with 18–30% efficiency, though germline transmission was not shown ( Oginuma et al, 2022 ). Moreover, knock-in of a long (1.5 kb) insertion was achieved for a specific locus with ~11% efficiency and successful germline transmission (germline transmission rate not shown) ( Krug et al, 2023 ). Our approach for CRISPR/Cas9-mediated knock-in in killifish allows long insertions (up to 2 kb), has >40% efficiency, and high germline transmission rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, longer CRISPR/Cas9-mediated knock-in insertions (~1 kb) were achieved in killifish (in F0 individuals) with 18–30% efficiency, though germline transmission was not shown ( Oginuma et al, 2022 ). Moreover, knock-in of a long (1.5 kb) insertion was achieved for a specific locus with ~11% efficiency and successful germline transmission (germline transmission rate not shown) ( Krug et al, 2023 ). Our approach for CRISPR/Cas9-mediated knock-in in killifish allows long insertions (up to 2 kb), has >40% efficiency, and high germline transmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have developed different CRISPR/Cas9-mediated long insertion knock-in approaches not only in killifish but also in other teleost species, such as zebrafish and medaka ( Gutierrez-Triana et al, 2018 ; Krug et al, 2023 ; Oginuma et al, 2022 ; Seleit et al, 2021 ; Wierson et al, 2020 ). Key points of difference between these approaches include (1) type of donor repair template – plasmid donor (with in vivo linearization) ( Oginuma et al, 2022 ; Wierson et al, 2020 ), dsDNA PCR amplification product ( Gutierrez-Triana et al, 2018 ; Krug et al, 2023 ; Seleit et al, 2021 ), or cloning-free synthetic dsDNA (as reported here), (2) use of chemical modification on linear dsDNA HDR repair template to prevent unwanted integration events (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted May 1, 2023. ; https://doi.org/10.1101/2023.05.01.538839 doi: bioRxiv preprint heterogeneity of cancer and metastasis. Together, we add to the continently expanding toolkit for the killifish model system [64][65][66][67] , by providing a transformative resource for advanced colorbased anatomical and lineage analyses during vertebrate aging and disease.…”
Section: Discussionmentioning
confidence: 99%